Copolymerization of ε-caprolactone with Epichlorohydrin by a Green Catalyst, Maghnite - Abdelghani Bouchama; Mohammed Issam Ferrahi; Mohamed Belbachir (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2012)
Most of the cationic initiators used in the synthesis of copolymers are expensive. They may be poisoned by products of the reaction or impurities present in the monomer feed, and contain heavy metals, such as chromium, mercury, antimony, etc., that presents environmental disposal problems for the user. Maghnite is a montmorillonite sheet silicate clay that is exchanged with protons to produce Maghnite-H+ (Mag-H+). This non-toxic and cheaper cationic catalyst was used for the copolymerization of ε-caprolactone (CL) with epichlorohydrin (ECH). The effects of the amounts of Mag-H+ and the temperature on the synthesis of poly (ε-caprolactone-co-epichlorohydrin) were studied. Increasing Maghnite-H+ proportion and temperature produced the increase in copolymerization yield. The copolymer obtained was characterized by 1H-NMR and IR spectroscopy. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)